2019
DOI: 10.1111/petr.13413
|View full text |Cite
|
Sign up to set email alerts
|

Ofatumumab in post‐transplantation recurrence of focal segmental glomerulosclerosis in a child

Abstract: FSGS is a potentially devastating form of nephrotic syndrome. Treatment of SRNS can be difficult, especially post‐transplantation. The current therapy of post‐transplant SRNS includes plasmapheresis, ACE‐I, CNI, and monoclonal antibodies (rituximab). Patients who are refractory to these interventions have limited therapeutic alternatives. We present a case of a patient with SRNS secondary to FSGS. He did not respond to immunosuppressive medications prior to transplant, progressed to ESRD, and was started on ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 22 publications
0
13
0
1
Order By: Relevance
“…The roles of pre-emptive plasmapheresis (pre and/or post-transplantation), immunoadsorption therapy, and other novel options such as ofatumumab or B7-1 blockers (abatacept and belatacept) to prevent disease recurrence or to treat recurrence appear promising but the efficacy of these treatments remain debatable and not always consistent or supported in subsequent studies (98105). Ofatumumab, an anti-CD20 monoclonal antibody that induces profound B cell depletion appears promising in the prevention ( n = 1) and treatment ( n = 2, achieved partial remission) of recurrent FSGS occurring post-kidney transplant but this needs to be confirmed in large studies (103, 106, 107). The initial treatment success surrounding the efficacy of abatacept, an inhibitor of B7-1 co-stimulatory molecule in achieving clinical remission in 5 patients with FSGS (4 patients with rituximab-resistant recurrent FSGS post-kidney transplant and 1 patient with steroid-resistant primary FSGS; all with positive B7-1 immunostaining of podocytes) has not been corroborated in other cohorts (100).…”
Section: Introductionmentioning
confidence: 99%
“…The roles of pre-emptive plasmapheresis (pre and/or post-transplantation), immunoadsorption therapy, and other novel options such as ofatumumab or B7-1 blockers (abatacept and belatacept) to prevent disease recurrence or to treat recurrence appear promising but the efficacy of these treatments remain debatable and not always consistent or supported in subsequent studies (98105). Ofatumumab, an anti-CD20 monoclonal antibody that induces profound B cell depletion appears promising in the prevention ( n = 1) and treatment ( n = 2, achieved partial remission) of recurrent FSGS occurring post-kidney transplant but this needs to be confirmed in large studies (103, 106, 107). The initial treatment success surrounding the efficacy of abatacept, an inhibitor of B7-1 co-stimulatory molecule in achieving clinical remission in 5 patients with FSGS (4 patients with rituximab-resistant recurrent FSGS post-kidney transplant and 1 patient with steroid-resistant primary FSGS; all with positive B7-1 immunostaining of podocytes) has not been corroborated in other cohorts (100).…”
Section: Introductionmentioning
confidence: 99%
“…One patient had post-transplant recurrent FSGS (6,11). Gastrointestinal complications such as nausea, vomiting, and abdominal pain were reported in some studies (1,13,16).…”
Section: N 5 Study Selectionmentioning
confidence: 95%
“…Another 14 items were removed after reviewing the full text of papers because the topics did not fit our study subject. Finally, 11 studies were selected in our systematic review (1,(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Figure 1 demonstrates the study selection approach.…”
Section: N 5 Study Selectionmentioning
confidence: 99%
“…Even though u-PCR remained at 3-6 g/g, IAds were not reinitiated and creatinine remained stable at 100-110 umol/l with serum albumin > 30 g/l. Further reports on the use of OFA in the recurrence of FSGS postrenal transplant [15][16][17] demonstrated that patients were able to achieve partial or full remission. The details of these case reports can be found in Table 1.…”
Section: N D H a D R E C E I V E D C Y C L O P H O S P H A M I D E ( mentioning
confidence: 98%